Identifying and managing project risk : essential tools for failure-proofing your project - Kendrick, Tom (AMACON, 2009)
"As a project manager, you know that complicated projects are inherently risky business. Between time constraints, technical challenges, and resource difficulties, things that can go wrong often do-which is why one of the most important parts of your job is considering the possible risks involved at every point in the process." "Fully updated and consistent with the very latest Guide to the Project Management Body of Knowledge (PMBOK Guide), Identifying and Managing Project Risk takes you through every phase of a project, helping you guard against failure by improving and increasing your risk analysis capabilities."